Financial Performace and Systemic Risk Effect On Stock Return (Case Study on Oil and Gas Companies Listed In IDX Year 2011-2016) - Dede Hertina; Mohamad Bayu Herdiawan Hidayat (Perisai : Islamic Banking and Finance Journal, 2018)
This study aimed to determine whether the return on assets, debt to equity ratio, and systematic risk effected on stock returns on oil and gas companies listed on the Stock Exchange period 2011-2016. The research method used was descriptive method verifikatif with research sample as much as 5 oil and gas company. The technique of selecting the sample used purposive sampling, while the method of analysis used was analaisis regresi panel data at significance level 5%, by using Eviews9. Partial result shows that Return On Asset was not influential to stock return and DER have negative and significant effect to stock return, while Beta had positive and significant effect to stock return and simultaneously Return On Asset, DER, and beta have positive effect to stock return.